Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1073/pnas.0904128106
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic carbon and anthropogenic pollutants combine to form a cooling haze over the southeastern United States

Abstract: Remote sensing data over North America document the ubiquity of secondary aerosols resulting from a combination of primary biogenic and anthropogenic emissions. The spatial and temporal distribution of aerosol optical thickness (AOT) over the southeastern United States cannot be explained by anthropogenic aerosols alone, but is consistent with the spatial distribution, seasonal distribution, and temperature dependence of natural biogenic volatile organic compound (BVOC) emissions. These patterns, together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
305
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(343 citation statements)
references
References 53 publications
23
305
9
Order By: Relevance
“…Furthermore, the distribution of the predicted mean gaseous MAE (Fig. 5A) matches the spatial patterns of enhanced summertime aerosol optical thickness over the southeastern United States observed by Goldstein et al (43) (see SI Text for spatial distribution of other isoprene-derived high-NO x products), likely linking our observations with the dominant summertime regional aerosol and the importance of biogenic volatile organic compound-anthropogenic interactions in radiative forcing in climate models. Taken together with the recent detection of isoprene epoxydiols under low-NO conditions (9-11), identification of MAE also implies epoxides derived from the oxidation of isoprene play a major role as SOA precursors.…”
supporting
confidence: 52%
“…Furthermore, the distribution of the predicted mean gaseous MAE (Fig. 5A) matches the spatial patterns of enhanced summertime aerosol optical thickness over the southeastern United States observed by Goldstein et al (43) (see SI Text for spatial distribution of other isoprene-derived high-NO x products), likely linking our observations with the dominant summertime regional aerosol and the importance of biogenic volatile organic compound-anthropogenic interactions in radiative forcing in climate models. Taken together with the recent detection of isoprene epoxydiols under low-NO conditions (9-11), identification of MAE also implies epoxides derived from the oxidation of isoprene play a major role as SOA precursors.…”
supporting
confidence: 52%
“…This theory is supported by the strong winter-to-summer seasonality in satellite-derived aerosol optical depth (AOD) that spatially and temporally matches biogenic volatile organic compound (BVOC) emissions in the region (Goldstein et al, 2009). A potential source of this summertime aerosol could be enhanced production of secondary organic aerosols (SOA) formed by the oxidation of volatile organic compounds (VOC) emitted from vegetation in the presence of anthropogenic pollutants from urban areas (Volkamer et al, 2006;Hoyle et al, 2011).…”
Section: Introductionmentioning
confidence: 79%
“…This notation is supported by (i) a recent aircraft study that observed a substantial enhancement in isoprene SOA aloft in the presence of anthropogenic NO x , 3 and (ii) discrepancies between satellite retrievals of aerosol optical thickness and surface organic aerosol measurements in the southeast US that imply there must be an altitudinal dependence in the SOA source. 4 …”
Section: Mpan (mentioning
confidence: 99%